PERANCANGAN FILM DOKUMENTER BATAGAK PANGULU DATUAK BASA SUKU SIKUMBANG DI NAGARI SIKUMBANG BUKIK KECAMATAN PALEMBAYAN - HAYYU MARDHATILLAH, Hendra Afriwan, S.Sn., M.Sn., Dini Faisal, S.Ds., M.Ds. (DEKAVE : Jurnal Desain Komunikasi Visual, 2016)
Lack of understanding of the target audience and not optimal media in disseminating information about Batagak pangulu a major factor in designing a documentary film writer dokumenter Batagak Pangulu Datuak Basa Suku Sikumbang Di Nagari Sikumbang Bukik Kecamatan Palembayan. Batagak pangulu is made in the form of a documentary film aimed so that people can more easily understand the activities Batagak pangulu and preserve the values that tradition , supported by several other media that help the major media to introduce the subject to the target audience , namely posters , stickers , T-shirts , bags , CD covers , CD labels , wrist bands ( bracelets ) , and the backdrop. Data collection methods used were interviews , observation , documentation , books and the internet . Data analysis methods were used that approach 5w + 1h that is what ( what ) , who ( who) , when ( when) , where ( in which ) , why ( why ) and how ( how ) .Keywords: Documentary Film, Batagak pangulu